1995
DOI: 10.1111/j.1525-1446.1995.tb00007.x
|View full text |Cite
|
Sign up to set email alerts
|

A Care Plan for Children with Tuberculosis

Abstract: Tuberculosis (TB) increased 34.1% among children 5 to 14 years old and 36.1% among those 0 to 4 years old in 1992 (American Academy of Pediatrics, 1994). In light of this resurgence, a care plan for children with TB has been developed. Health care workers, especially community health nurses, must be knowledgeable about the transmission, pathogenesis, diagnosis, and treatment of this disease. Armed with this knowledge, an effective teaching program for nurses must be initiated to interrupt the spread of tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Tuberculosis is common in developing countries and although once rare in developed countries, the incidence is increasing and it has become a health concern throughout the world. [5][6][7][8] Renal TB is uncommon in children, but needs to be considered especially in disseminated disease as specific interventions would be required. [1][2][3] There is usually a long latent period of 2-20 years between infection and clinical features of renal TB.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is common in developing countries and although once rare in developed countries, the incidence is increasing and it has become a health concern throughout the world. [5][6][7][8] Renal TB is uncommon in children, but needs to be considered especially in disseminated disease as specific interventions would be required. [1][2][3] There is usually a long latent period of 2-20 years between infection and clinical features of renal TB.…”
Section: Discussionmentioning
confidence: 99%
“…For those nurses who suggested that a lack of privacy for administering medications was an issue, the stigma attached to TB was the concern. It is important that the caregiver, in any treatment situation, is empathetic (Buttaro, Ezell, & Gray, 1995). Empathy is key in dealing with families as well.…”
Section: Discussionmentioning
confidence: 99%
“…Each student had differing needs, which could be addressed coherently by a care plan (Fagan, 1995). This care plan should have addressed how each student took his or her medications, convenient times for the student and nurse, medications and doses taken, follow-up tests needed, reminders for clinic appointments and testing, and treatment options for other members of the family who may be in school (Buttaro et al, 1995). Pediatric care plans were already existent at the NJMS NTBC clinic but required the inclusion of the school nurse role in treatment.…”
Section: Discussionmentioning
confidence: 99%